Interactive Virtual Campus Tour using Panoramic Video: A Heuristic Evaluation - Osman, Aznoora; Iskak, Nur Izlin; Abdul Wahab, Nadia; Ibrahim, Norfiza (UiTM Cawangan Perlis, 2020)
Difficulty in finding the destination around a campus is a common problem faced by students, staffs and visitors of a university. Outdated signboards, confusing building architecture and layout, and bad weathers are just some of the hindrance to find location for people who are unfamiliar with the campus area. To solve the problem, virtual campus tour is chosen because it can also be embedded into a university website, or use as a stand-alone app. The virtual campus tour which can be accessed as mobile app or web app, can help users in visualizing their journey around campus because it was developed using collections of panoramic video footage, which allows user to watch in 360-degree view of selected campus area. Administrative building, academic blocks and residential college are some of the destinations included in the tour. Due to the need to create and test components of the product iteratively, Agile method was employed as the development methodology. Agile supports high integration between development and testing phase. This paper discusses the development process of the virtual campus tour, which were encapsulated in the four phases of Agile methodology, requirement phase, design phase, development phase and test feedback phase.